(untitled) (Cuea Journal of Business and Economics, 2025)
County governments in the North Rift Region face low employee engagement due to poor recruitment practices and limited staff development. Inadequate supervisory support and unclear expectations further contribute to high turnover and substandard service delivery. So, the purpose of this research was to find out how county governments in Kenya's North Rift Region deal with staff engagement and how training affects it. Social Exchange Theory served as the data foundation for the research. One hundred and ninety-nine employees were the intended recipients. In order to choose these 385 workers, researchers employed both cluster and basic random sampling methods. Structured questionnaires were used to gather the data. The research instruments' validity and reliability were tested in a pilot study. To determine the nature of the link between the variables, regression analysis was carried out. The data was displayed in tabular form. Statistical analysis showed that the model well described the connection between the dependent variable and participation (F = 142.299, p = 0.000). Training employees significantly increased their level of involvement, according to regression analysis (B = 0.093, p = 0.046). In view of the findings, the study recommends that county governments in the North Rift Region should invest in structured and continuous employee training programs to enhance staff engagement